2004
DOI: 10.1021/ma035838w
|View full text |Cite
|
Sign up to set email alerts
|

A New Double-Responsive Block Copolymer Synthesized via RAFT Polymerization:  Poly(N-isopropylacrylamide)-block-poly(acrylic acid)

Abstract: Poly(N-isopropylacrylamide)-block-poly(acrylic acid), PNIPAAm-b-PAA, with low polydispersity was prepared by reversible addition-fragmentation chain transfer (RAFT) polymerization in methanol. The block copolymers respond to both temperature and pH stimuli. The behavior of the doubleresponsive block copolymers in solution was investigated by dynamic light scattering, temperature-sweep NMR, cryogenic transmission electron microscopy, and IR spectroscopy. The block copolymers form micelles in aqueous solutions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
453
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(473 citation statements)
references
References 12 publications
18
453
1
1
Order By: Relevance
“…However, since 2000, living polymerization has become possible for poly(NIPAM), [3][4][5][6]74 and many related polymers have since been prepared. [7][8][9][10] We conducted a systematic investigation of the vinyl ether system, studying the effect of the molecular weight, MWD, and other properties such as the sequence distribution. For example, the investigation of the effect of the distribution interestingly showed that a narrow MWD corresponded to high sensitivity in phase separation.…”
Section: Synthesis and Self-association Of Stimuli-responsive Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since 2000, living polymerization has become possible for poly(NIPAM), [3][4][5][6]74 and many related polymers have since been prepared. [7][8][9][10] We conducted a systematic investigation of the vinyl ether system, studying the effect of the molecular weight, MWD, and other properties such as the sequence distribution. For example, the investigation of the effect of the distribution interestingly showed that a narrow MWD corresponded to high sensitivity in phase separation.…”
Section: Synthesis and Self-association Of Stimuli-responsive Polymersmentioning
confidence: 99%
“…In fact, recent progress in living polymerization, particularly in controlled/living radical polymerization, 2 has permitted the precise design [3][4][5][6] and synthesis of various block copolymers for self-assembly. [7][8][9][10] Living cationic polymerization, known for over 20 years, 11 is another powerful tool for preparing various smart polymers with functional groups. In the 1980s, Higashimura et al 12 (the Kyoto group) and Kennedy et al 13,14 (the Akron group) independently discovered the living cationic polymerization of vinyl ethers (HI/I 2 initiating system) and isobutene (cumyl acetate/BCl 3 initiating system), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Although great interest has focused on the controlled synthesis of the NIPAM-based polymer, it has not been achieved because PNIPAM and its copolymers have been traditionally prepared using conventional free radical polymerization. However, in recent years, the PNIPAM with a well-defined molecular weight and polydipersity has been provided through living anionic polymerizations 17 and living radical polymerizations, such as the niroxide-mediated radical polymerization, [18][19][20] the reversible addition-fragmentation chain transfer polymerization, [21][22][23][24][25][26] and the atom transfer radical polymerization (ATRP). [27][28][29][30][31][32] In general, the living nature of polymerization affords well-defined macromolecular architectures, therefore, it is interesting to prepare PNIPAMs with specific structures and properties.…”
Section: Introductionmentioning
confidence: 99%
“…In a contrasting case, Schilli et al examined doubly responsive poly(acrylic acid)-b-poly(NIPAM) (PAA-b-PNIPAM) block copolymers. With increasing pH from 4.5 to approximately 5-7, the LCST of the PNIPAM increased from 29 to 35 • C [77]. In a system applying similar NMP techniques that was used here, PAA-b-poly(diethyl acrylamide) (PAA-b-PDEAAm) was made in dispersion and the hydrodynamic radius was measured as a function of pH at different temperatures (15, 25 and 50 • C) [78].…”
Section: Block Copolymers With Both Ph and Temperature Sensitivitiesmentioning
confidence: 99%